2012
DOI: 10.1038/nature11658
|View full text |Cite
|
Sign up to set email alerts
|

DNA-repair scaffolds dampen checkpoint signalling by counteracting the adaptor Rad9

Abstract: In response to genotoxic stress, a transient arrest in cell cycle progression enforced by the DNA damage checkpoint (DDC) signaling pathway positively contributes to genome maintenance1. Because hyperactivated DDC can lead to a persistent and detrimental cell cycle arrest2,3, cells must tightly regulate the activity of DDC kinases. Despite their importance, the mechanisms for monitoring and modulating DDC signaling are not fully understood. Here we show that DNA repair scaffolding proteins Slx4 and Rtt107 prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
177
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(196 citation statements)
references
References 30 publications
(41 reference statements)
17
177
0
Order By: Relevance
“…Accumulating evidence suggests that scaffold-like proteins, such as those harbouring BRCT domains 2 , are involved in the signal transduction pathways of DDRs by recruiting various components and regulators. A recent study has revealed that DNA repair scaffolds directly modulate the checkpoint signalling pathway in budding yeast 3 . Therefore, the functions of scaffoldlike proteins in the DDR play essential roles in the coordination of cellular responses to maintain homeostasis.…”
mentioning
confidence: 99%
“…Accumulating evidence suggests that scaffold-like proteins, such as those harbouring BRCT domains 2 , are involved in the signal transduction pathways of DDRs by recruiting various components and regulators. A recent study has revealed that DNA repair scaffolds directly modulate the checkpoint signalling pathway in budding yeast 3 . Therefore, the functions of scaffoldlike proteins in the DDR play essential roles in the coordination of cellular responses to maintain homeostasis.…”
mentioning
confidence: 99%
“…74 The latter modification, particularly at Serine 486 of Slx4, contributes to its interaction with Dpb11. 77,79 These studies also suggest that phosphorylated Slx4 likely directly binds to Dpb11, while Rtt107 stabilizes this interaction. The Slx4-Dpb11 interaction is conserved as phosphorylated human SLX4 also associates with TopBP1.…”
Section: The Rtt107 and Slx4 Association And Its Functions In Conjuncmentioning
confidence: 73%
“…77,80,81 An underlying mechanism may be that Slx4 and Rad9 compete for binding to BRCT1-2 of Dpb11, though Slx4 can also associate with BRCT3-4 of Dpb11. 77,79 It appears that BRCT1-2 and BRCT3-4 of Dpb11 can engage Slx4 and the 9-1-1 complex. 77,79,80 As such, Dpb11 can bridge Slx4 and 9-1-1 (Fig.…”
Section: The Rtt107 and Slx4 Association And Its Functions In Conjuncmentioning
confidence: 99%
See 2 more Smart Citations